KARAKTERISTIK GAMBUT KAWASAN HIDROLOGIS KAHAYAN SEBANGAU PADA SIFAT BIOLOGI DAN GUGUS FUNGSIONALNYA - Puspitorini, Palupi; Iqbal Pradhipta, Gelvin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
The purpose of the study was to determine the differences in several soil biological properties and peat functional groups based on the location of soil formation (tidal peat, transitional peat, and inland peat). The study was conducted on peat soils in the Kahayan Sebangau Hydrological area, Central Kalimantan, from June to August 2018. The research method is laboratory observation to determine the biological and chemical properties of soil from each soil sample from each location, soil chemical analysis using the FTIR method and biological properties analysis using the Count Cup method. The variables observed were Total Microbiology, Total Fungi, Total Bacteria, Total Respiration and functional groups at Tidal (PS), Transitional (PR) and Inland (PD) peat locations at depths of 0-25 cm and 25-50 cm. The results showed that based on the location of soil formation (tidal peat, transitional peat, and inland peat) the total population of microorganisms, fungi, bacteria and total respiration was most found in tidal peat, based on the sampling depth that the total population of microorganisms, fungi, bacteria and total respiration was most found at a depth of 0 - 25 cm from its surface, from the results of FTIR analysis of the main functional groups On peat soils that of the three tidal, transitional and inland peat areas that the largest area in the three tidal, transitional and inland areas is dominated by fatty acid and wax functional groups with wavelengths of 3400 – 3000 cm-1. From the results of FTIR analysis at sample depths of 0-25 cm and 25-50, the highest values are wavelengths of 3400-3000 and 3000-2800 cm-1, where in this layer the main characteristics are fatty acids and waxes.